2022
DOI: 10.1111/dom.14725
|View full text |Cite
|
Sign up to set email alerts
|

Weight regain and cardiometabolic effects after withdrawal of semaglutide: The STEP 1 trial extension

Abstract: Aim: To explore changes in body weight and cardiometabolic risk factors after treatment withdrawal in the STEP 1 trial extension.Materials and Methods: STEP 1 (NCT03548935) randomized 1961 adults with a body mass index ≥ 30 kg/m 2 (or ≥ 27 kg/m 2 with ≥ 1 weight-related co-morbidity) without diabetes to 68 weeks of once-weekly subcutaneous semaglutide 2.4 mg (including 16 weeks of dose escalation) or placebo, as an adjunct to lifestyle intervention. At week 68, treatments (including lifestyle intervention) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
140
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 281 publications
(194 citation statements)
references
References 24 publications
8
140
0
Order By: Relevance
“…In contrast to findings with behavioral 20 22 and other pharmacological interventions 10 , 12 , 13 , the similar mean weight loss achieved with semaglutide 2.4 mg in STEP 5 at weeks 52 and 104 (–15.6% and –15.2%, respectively) suggests that, on average, there is minimal weight regain over 104 weeks when once-weekly semaglutide therapy is continued. When interpreted together with the findings of the STEP 4 withdrawal trial and STEP 1 off-treatment extension study, which both showed weight regain after semaglutide discontinuation (after 20 weeks’ treatment in STEP 4 and 68 weeks’ treatment in STEP 1) 23 , 24 , these results support the benefit of continued semaglutide treatment for sustained weight loss.…”
Section: Discussionmentioning
confidence: 55%
“…In contrast to findings with behavioral 20 22 and other pharmacological interventions 10 , 12 , 13 , the similar mean weight loss achieved with semaglutide 2.4 mg in STEP 5 at weeks 52 and 104 (–15.6% and –15.2%, respectively) suggests that, on average, there is minimal weight regain over 104 weeks when once-weekly semaglutide therapy is continued. When interpreted together with the findings of the STEP 4 withdrawal trial and STEP 1 off-treatment extension study, which both showed weight regain after semaglutide discontinuation (after 20 weeks’ treatment in STEP 4 and 68 weeks’ treatment in STEP 1) 23 , 24 , these results support the benefit of continued semaglutide treatment for sustained weight loss.…”
Section: Discussionmentioning
confidence: 55%
“…Pharmacological activation of the widespread distribution of GLP‐1 receptors within the CNS, including the hypothalamus, promotes satiety and controls appetite and body weight 8 . Weight regain appears to be common upon cessation of treatment with semaglutide, 9 and long‐term weight loss maintenance is likely to require continuous use.…”
Section: Discussionmentioning
confidence: 99%
“…Among 327 persons having BMI >30 kg/m 2 with at least one weight‐related comorbidity, but not having diabetes, treated with semaglutide 2.4 mg weekly vs. placebo for 68 weeks, 52 weeks after discontinuation of treatment the placebo group returned to baseline, and the semaglutide group, whose BMI had decreased from 37.6 to 31.2, had an increase in BMI to 35. Systolic and diastolic blood pressure, HbA1c, lipids, and C‐reactive protein all similarly returned toward or above baseline, 13 suggesting that such treatment likely is required in an ongoing fashion for persons with diabetes as well.…”
Section: Therapymentioning
confidence: 91%